2018
DOI: 10.1038/s41598-018-33467-y
|View full text |Cite
|
Sign up to set email alerts
|

Current-driven production of vortex-antivortex pairs in planar Josephson junction arrays and phase cracks in long-range order

Abstract: Proliferation of topological defects like vortices and dislocations plays a key role in the physics of systems with long-range order, particularly, superconductivity and superfluidity in thin films, plasticity of solids, and melting of atomic monolayers. Topological defects are characterized by their topological charge reflecting fundamental symmetries and conservation laws of the system. Conservation of topological charge manifests itself in extreme stability of static topological defects because destruction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 55 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…While the quantum phases [10][11][12][13][14][15][16]25] and the vortex dynamics [26][27][28][29][30][31] under magnetic fields have been intensively studied in 2D superconductors, the dynamical properties at high current and zero magnetic field have been largely unexplored. It has been well known that in 2D superconductors the zero-ohmic-resistance state is achieved by the Berezinskii-Kosterlitz-Thouless (BKT) transition [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the quantum phases [10][11][12][13][14][15][16]25] and the vortex dynamics [26][27][28][29][30][31] under magnetic fields have been intensively studied in 2D superconductors, the dynamical properties at high current and zero magnetic field have been largely unexplored. It has been well known that in 2D superconductors the zero-ohmic-resistance state is achieved by the Berezinskii-Kosterlitz-Thouless (BKT) transition [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of vortices, whether in zero or finite magnetic fields, has been a longstanding research field from the viewpoint of fundamental interests in interacting particles as well as application of superconductors at high current density. While the dynamics of slow Abrikosov vortices in magnetic field (B), containing the plastic flow state and the moving lattice state, has been thoroughly investigated in various 2D superconductors [26][27][28], there are still many ongoing discussions on the dynamics of ultrafast vortices under high current density [31,41]. One of the typical examples is the sudden jump of voltage induced by the vortex motion as observed in various superconductor films [29,30,[42][43][44], which was interpreted based on the flux-flow instability predicted by Larkin and Ovchinnikov in the early stages [45] and was recognized later as the possible appearance of the phase slip lines [46], namely, flow channels of the Josephson-like (kinematic) vortices [47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…Generation of V-AV pairs by a moving vortex pertains to a broader issue of stability of driven topological defects that can destroy global long range order in a way similar to the crack propagation resulting from the pileup of dislocations of opposite polarity 46 . Such process was observed in simulations of vortices in long JJs and planar JJ arrays where driven vortices cause propagating phase cracks in superconducting long range order 29,32 . A question whether a fast Josephson vortex can initiate the V-AV pair production in layered superconductors is of interest to the theory of nonlinear flux flow of vortices along the ab planes in high-T c cuprates and pnictides or artificial multilayer structures.…”
Section: Introductionmentioning
confidence: 78%
“…One of the outstanding questions is * asheikhz@odu.edu † gurevich@odu.edu whether this topologically protected stability of a moving vortex remains preserved at any current below the depairing limit or there is a terminal velocity above which a uniformly moving vortex cannot exist. As far as the Josephson vortices are concerned, numerical simulations of long underdamped junctions 29 , planar JJ arrays [30][31][32] and a few coupled JJs [33][34][35][36][37] , and discrete sine-Gordon systems 38,39 , have shown that there is indeed a terminal velocity v c above which uniform motion of a vortex driven by a dc current breaks down due to Cherenkov radiation. The Cherenkov radiation of a vortex moving with a constant velocity v is characteristic of high-J c Josephson junctions (JJ) or arrays of coupled JJs in which the phase velocity of electromagnetic waves v p (k) decreases as the wave number k increases [40][41][42][43][44][45] , so that the Cherenkov condition v > v p (k) can be more easily satisfied at short wavelengths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation